DEALING WITH INSULIN RESISTANCE AMONG POLYCYSTIC OVARIAN SYNDROME PATIENT - Dr Firdous Ara; Dr Maryam Shoaib; Dr Rizwana Naz; Dr Sadia Ghilzai; Dr Saira Qadar; Dr Sadiq Jan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Insulin resistance is a key factor in the pathophysiology of PCOS and is associated with various metabolic complications, including type II diabetes, obesity, and cardiovascular diseases. Objective: The objective of this study is to evaluate effectiveness of multimodal treatment for managing insulin resistance in patients with Polycystic Ovarian SyndromeMethodology: It is a randomized control study conducted at Sandeman Provincial Hospital Quetta from 1st May 2023 to 30th April 2024. 100 participants received tablet Metformin 500mg thrice a day along with a low calorie diet and exercise plan. Participant were treated for 3 months and their BMI, caloric intake, serum FSH, LH, testosterone, fasting blood glucose and fasting insulin levels were measured. The data analysis was conducted using the Statistical Package for Social Sciences version 24.00. The p value of ≤ 0.5 was considered significant.Result: The average age of participants was 26.78±6.54years. There was reduction in BMI from 30.13±5.41 to 26.2±2.9, Homeostasis Model Assessment of Insulin Resistance decreased significantly from 4.2±0.8 to 2.1±0.5, with FSH increasing from 5.1±1.7U/L to 7.9±2.8U/L(P = 0.02) and LH decreasing from 9.2±5.5U/L to 6.5±1.7U/L(P= 0.02), indicating improved ovarian function and hormonal balance. Total testosterone levels also decreased from 76.3±12.4 pg/ml to 63.8±9.7pg/ml. menstrual regularity and ovulation restoration was observed in 71% and 59% of participants respectively. Conclusion: Comprehensive management strategies integrating dietary adjustments, regular physical activity, and pharmacological treatment are foundational in enhancing insulin sensitivity and mitigating risks such as menstrual irregularities and hyper-androgenism in patients with Polycystic Ovarian Syndrome.